Makhzan al Adviyeh and Pointing to the Scientific Names of Medicinal Plants for the First Time in a Persian Book - Mohammad Reza Shams Ardakani; Fatemeh Farjadmand; Roja Rahimi (Tehran University of Medical Sciences, 2018)
Makhzan al-Adviyeh is a medicinal book on simple drugs written with eloquent and fluent prose in Persian by Mohammad Hossein Aghili Khorasani Shirazi in 12th AH century. This book is for sure one of the most comprehensive Persian books on medicinal simple drugs and is very much addressed by traditional medicine researchers. One of the interesting points about this book is the consideration of the scientific names of some of the herbs which are being noted in a Persian book for the first time by Aghili. In this paper, this subject has been addressed together with collecting and describing information regarding the herbs mentioned by their scientific names in the book of Makhzan al-Adviyeh.